(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the story "Shubha" by Rabindranath Tagore, a great figure of world literature, from an artistic and psychological perspective. The focus of the study is on the role of the main character of the work - the mute girl Shubha - in the classification of images, her mental suffering and lack of communication with society. The article reveals the author’s artistic skill, individual style in creating characters, and the artistic function of non-verbal means of communication. The results of the study are based on philological analysis.